1989
DOI: 10.1161/01.cir.80.4.883
|View full text |Cite
|
Sign up to set email alerts
|

Blunted sympathetic response to cardiopulmonary receptor unloading in hypertensive patients with left ventricular hypertrophy. A possible compensatory role of atrial natriuretic factor.

Abstract: To investigate whether or not hypertension with left ventricular hypertrophy (LVH) modifies the mechanisms underlying the vascular adjustments to orthostatic stress, we evaluated the hemodynamic and hormonal effects ofgraded lower-body negative pressure (LBNP) (-10 and -40 mm Hg) before and after sympathetic blockade in 10 hypertensive patients with LVH and in five age-and sex-matched normotensive subjects. In control conditions, LBNP elicited comparable vasoconstrictor responses in the forearm in the two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…), and quantified by a current produced on exposure of the column effluent to oxidizing and then reducing potentials connected in series (Coulochem II, ESA, Inc., Bedford, Mass.). 11 Recovery through the alumina extraction step, calculated using dihydroxybenzylamine as an internal standard, ranged 60-70%; each sample was corrected for its recovery, and detection limits were 3 pg. Intra-assay and interassay variation coefficients were for norepinephrine 4.1% and 9.8%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…), and quantified by a current produced on exposure of the column effluent to oxidizing and then reducing potentials connected in series (Coulochem II, ESA, Inc., Bedford, Mass.). 11 Recovery through the alumina extraction step, calculated using dihydroxybenzylamine as an internal standard, ranged 60-70%; each sample was corrected for its recovery, and detection limits were 3 pg. Intra-assay and interassay variation coefficients were for norepinephrine 4.1% and 9.8%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…36 The exaggerated vascular resistance response to head-up tilt in hypertension has not been explained by a greater sympathetic response. 37 Thus, mechanisms other than autonomic neural regulation should be taken into consideration. London et al 36 suggested that vascular wall hypertrophy might amplify the vascular resistance responses to head-up tilt.…”
Section: Discussionmentioning
confidence: 99%
“…Right atrial pressure and venous plasma norepinephrine levels were measured in control conditions and during LBNP at -10 mm Hg before and after a 3-day digitalis treatment at the doses reported Plasma norepinephrine assay was performed with reverse-phase high-performance liquid chromatography with electrochemical detector as previously described. 15 The sensitivity of the assay was 10 pg injected. Intra-assay and interassay variation coefficients for norepinephrine were …”
Section: Discussionmentioning
confidence: 99%